2008
DOI: 10.1007/s10653-008-9183-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk remaining from fine particle contaminants after vacuum cleaning of hard floor surfaces

Abstract: In the indoor environment, settled surface dust often functions as a reservoir of hazardous particulate contaminants. In many circumstances, a major contributing source to the dust pool is exterior soil. Young children are particularly susceptible to exposure to both outdoor derived soil and indoor derived dust present in the indoor dust pool. This is because early in life the exploratory activities of the infant are dominated by touching and mouthing behavior. Inadvertent exposure to dust through mouth contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…Iron and Mn are major components of soil minerals and have been noted to be abundant elements in the earth crust. 59 Our Fe and Mn concentrations were within typical soil concentration ranges, with all measurements for both of these PTE falling below the earth's crust and continental shale values respectively. Our dust samples were similarly not contaminated with Cu and Ni, with concentrations below typical soil concentrations and the reported SGVs (Table 3).…”
Section: Total Dust Metal Concentrationssupporting
confidence: 65%
“…Iron and Mn are major components of soil minerals and have been noted to be abundant elements in the earth crust. 59 Our Fe and Mn concentrations were within typical soil concentration ranges, with all measurements for both of these PTE falling below the earth's crust and continental shale values respectively. Our dust samples were similarly not contaminated with Cu and Ni, with concentrations below typical soil concentrations and the reported SGVs (Table 3).…”
Section: Total Dust Metal Concentrationssupporting
confidence: 65%
“…The highest concentration heavy metal obtained was Fe with the mean concentration 4225.33 mg/kg and followed by Al with the mean concentration of 1229.58 mg/kg. Both Al and Fe are abundant elements in the Earth's crust (AlKhashman, 2004;Hunt et al, 2008). These elements have been produced by alteraction (friction) and distributed or transported via wind blow and can be associated with soil or street dust.…”
Section: Heavy Metals Concentrationmentioning
confidence: 99%
“…For example, when considering removal by cleaning, Hunt et al found that mechanical cleaning did not completely remove SVOCs on surfaces because a significant portion of the compound was found in surface reservoirs such as carpet fibers or foam materials after a carpet vacuuming event. 13 Therefore, we use the term "non-mobile phase" to represent the portion of the compound partitioned into surface materials as opposed to the portion in dust or air.…”
Section: Introductionmentioning
confidence: 99%